Hinduism : A Very Short Introduction - Knott, Kim (Oxford, New York Oxford University Press, 2016)
Hinduism is practiced by about 80 percent of India's population, and by about 30 million people outside India. But how is Hinduism defined, and what basis does the religion have? In this Very Short Introduction, Kim Knott provides clear insight into the beliefs and authority of Hindus and Hinduism, and considers the ways in which it has been affected by colonialism and modernity. The author also considers the challenges posed to Hinduism at the end of the twentieth century as it spreads far beyond India, and as concerns are raised about issues such as dowry, death, caste prejudice, and the place of women in Hindu society.
Include Index and Illustration
Keywords: Hinduism